2006
DOI: 10.1002/jssc.200600149
|View full text |Cite
|
Sign up to set email alerts
|

High‐capacity purification of hen egg‐white proteins by ion‐exchange electrochromatography with an oscillatory transverse electric field

Abstract: Original PaperHigh-capacity purification of hen egg-white proteins by ion-exchange electrochromatography with an oscillatory transverse electric fieldThe ion-exchange electrochromatography with an oscillatory electric field perpendicular to the mobile-phase flow driven by pressure (pIEEC) was used to separate hen egg-white (HEW) proteins. The results were compared with those of normal ionexchange chromatography (IEC). The column was designed as three-compartment rectangular column of 2-mL with dimensions (leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…3, good model fitting to the breakthrough curves of BSA in the pIEEC was obtained with Eq. (10). This demonstrates the reasonability of the above analysis and Eq.…”
Section: Simulation Of Breakthrough Behaviorsupporting
confidence: 59%
See 3 more Smart Citations
“…3, good model fitting to the breakthrough curves of BSA in the pIEEC was obtained with Eq. (10). This demonstrates the reasonability of the above analysis and Eq.…”
Section: Simulation Of Breakthrough Behaviorsupporting
confidence: 59%
“…However, the driving effect decreases due to the decrease of the Peclet number as depicted by Eq. (10). So, the deviation of BSA distribution also decreases with increasing adsorption time (Fig.…”
Section: Protein Distribution In An Adsorbent Beadmentioning
confidence: 81%
See 2 more Smart Citations
“…HETP values for all solutes in the EC 5/10 column were similar to their corresponding values in the commercial HR 5/10 column, suggesting that both columns had equivalent separation efficiencies. In a chromatographic column with a rectangular cross‐section, EF always led to higher aggregation of the liquid‐phase flow and increased HETP values . In a theoretical way, Khirevich et al also demonstrated that the chromatographic performance depended critically on the column geometry in a (micro)channel packed with particles, and flow profiles of non‐cylindrical columns deviated greatly from those of cylindrical columns .…”
Section: Resultsmentioning
confidence: 99%